Molecular characterization of muscle-specific calmodulin-dependent protein kinases. - Leddy, John J. (University of Ottawa (Canada), 1999)
Activation of calmodulin-dependent protein kinase activity associated with rabbit skeletal muscle sarcoplasmic reticulum (SR) resulted in the phosphorylation of polypeptides of 450, 360, 165, 105, 89, 73, 60, 34 and 20 kDa. A membrane-bound 60 kDa, polypeptide contained both calmodulin (CaM) and ATP-binding domains and exhibited CaM-dependent autophosphorylation activity. A 73 kDa polypeptide was also found to bind CaM and undergo CaM-dependent autophosphorylation. Subcellular distribution of the 60 kDa kinase indicated the specific association of the polypeptide with the junctional face membrane of SR. The 73 kDa polypeptide tightly associated with membrane and not cytosolic fractions. We postulated that these kinases may be responsible for gating the Ca2+ release channel. The cDNAs encoding the CaM-dependent protein kinases from skeletal muscle were cloned. A clone, named SOCK was sequenced and characterized as a novel isoform of CaM-dependent protein kinases. The predicted amino acid sequence of SOCK showed that it was similar to the classical beta CaMKII isoform but contained a novel peptide sequence of 122 amino acids in the C terminus. This novel domain was enriched in proline residues and was homologous to SH3-binding domains containing the minimal consensus sequence P-X-X-P. Genomic cloning of SOCK indicated that the 122 amino acid sequence was generated via alternative splicing of three exons encoding the three proline-rich domains. GST-fusion proteins constructs revealed that SOCK, as well as the novel proline-rich region, bound to SH3 domains of the src family of tyrosine kinases. Furthermore, the SH3 domains could specifically bind the 73 and 60 kDa CaM kinases from soluble membrane extracts. The tissue distribution of SOCK indicated the presence of a 4.8 kb transcript expressed exclusively in skeletal, cardiac and smooth muscle. Cell fractionation studies showed that SOCK and src can be localized to similar cellular compartments in muscle cells. Binding of SOCK kinase to src resulted in the inhibition of CaM-dependent phosphorylating activity. Embryonal carcinoma P19 cells transfected with an expression plasmid carrying SOCK cDNA failed to differentiate along the mesodermal pathway but not the neuroectodermal pathway. These results indicate that SOCK represents a novel isoform of the beta CaM kinase II family that is uniquely structured and may participate to integrate calcium and tyrosine kinase signalling pathways in muscle systems. (Abstract shortened by UMI.)
Keywords: Biology, Molecular.